The effect of bank market power on economic growth in Africa: The role of institutions - Anthony Adu Asare Idun; Anthony Q. Q. Aboagye; Godfred A. Bokpin (Cogent Economics & Finance, 2020)
We provide empirical investigations into the role of political institutions in the bank market power-economic growth nexus using country-level data from 44 African countries from 2002 to 2015. We employed a dynamic GMM model to achieve the above objective. The results show that banks with market power in Africa induce economic growth. Also, institutional quality improvement causes positive economic growth and improves the degree with which banks with market power influence economic growth. The influence of institutional quality on economic growth, however, varies depending on specific institutional factors even when we differentiated the effect of the level of bank market power. In West Africa, banks with market power induce economic growth, but the less competitive nature in the banking environment of the other sub-regions discourages economic growth. The results call for policy directions that improve economic and political institutions towards improving effective intermediation in Africa. In West Africa, the Central Banks should come up with regulations targeting large banks with market power to channel funds into productive sectors. In other sub-regions, more competitive banking environments can harness financial resources into productivity growth. The implication is that, regulators and policymakers should implement sound institutional structures that would ensure tailor-made banking system structure to stimulate sustainable economic growth in Africa.
Keywords: 330; Africa; bank market power; economic growth; institutional quality; regional integration